Real-time ultrasound-guided thoracentesis in the intensive care unit: prevalence of mechanical complications (2020)
Background: The use of thoracic ultrasound during thoracentesis reduces complications. The aim of this study was to determine the prevalence of complications for real-time ultrasound-guided thoracentesis performed by intensivists. As a secondary objective, the change in oxygenation before and after the procedure was evaluated. Patients and methods: An observational prospective study was conducted. A total of 81 cases of real-time ultrasound-guided thoracentesis performed by intensivists in the intensive care unit (ICU) of Méderi Major University Hospital, Bogotá, Colombia, between August 2018 and August 2019 were analyzed. Thoracentesis performed by interventional radiologists and using techniques different from the focus of this study were excluded from the analysis. Results: There was one pneumothorax, for a prevalence rate of mechanical complications in this population of 1.2%. The mean partial oxygen pressure to inspired oxygen fraction ratio (PaO2/FiO2) prior to the procedure was 198.1 (95% CI 184.75–211.45), with a PaO2/FiO2 after the procedure of 224.6 (95% CI 213.08–226.12) (p and lt; 0.05). Conclusions: Real-time ultrasound-guided thoracentesis performed by intensivists is a safe procedure and leads to a significant improvement in oxygenation rates. Future studies are required to determine the impact of these results on other outcomes, such as mortality, ICU stay, and days of mechanical ventilation. © 2020, The Author(s).